High prevalence of spondyloarthritis-like MRI lesions in postpartum women: a prospective analysis in relation to maternal, child and birth characteristics. Issue 7 (16th April 2020) - Renson, Thomas; Depicker, Anaïs; De Craemer, Ann-Sophie; Deroo, Liselotte; Varkas, Gaëlle; de Hooge, Manouk; Carron, Philippe; Jans, Lennart; Herregods, Nele; Dehaene, Isabelle; Vandenberghe, Griet; Roelens, Kristien; et al.
Abstract : Objectives: Bone marrow oedema (BMO) on MRI of sacroiliac joints (SIJs) represents a hallmark of axial spondyloarthritis (SpA), yet such lesions may also occur under augmented mechanical stress in healthy subjects. We therefore sought to delineate the relationship between pregnancy/delivery and pelvic stress through a prospective study with repeated MRI. Results were matched with maternal, child and birth characteristics. Methods: Thirty-five women underwent a baseline MRI-SIJ within the first 10 days after giving birth. MRI was repeated after 6 months and, if positive for sacroiliitis according to the Assessment of SpondyloArthritis International Society (ASAS) definition, after 12 months. BMO and structural lesions were scored by three trained readers using the Spondyloarthritis Research Consortium of Canada (SPARCC) method. Results: Seventy-seven per cent of the subjects (27/35) displayed sacroiliac BMO immediately postpartum, 60% fulfilled the ASAS definition of a positive MRI. After 6 months, 46% of the subjects (15/33) still showed BMO, representing 15% (5/33) with a positive MRI. After 12 months, MRI was still positive in 12% of the subjects (4/33). Few structural lesions were detected. Intriguingly, in this study, the presence of BMO was related to a shorter duration of labour and lack of epidural anaesthesia. Conclusion: A surprisingly high prevalence of sacroiliac BMO occurs in women immediately postpartum. Our data reveal a need for a waiting period of at least 6 months to perform an MRI-SIJ in postpartum women with back pain. This study also underscores the importance of interpreting MRI-SIJ findings in the appropriate clinical context.